“Typing Ganteng” sebagai Representasi Personal Branding dan Strategi Komunikasi Interpersonal Generasi Z di Ruang Digital - Faiqotul Isma Dwi Utami; Ach Ilham Zubairi (ALAMTARA, 2025)
This study explores the phenomenon of Typing Ganteng, a digital typing style characterized by politeness, clarity, and aesthetic appeal, as a form of interpersonal communication and personal branding among Generation Z. Grounded in interpersonal communication theory and digital identity discourse, the research applies a qualitative phenomenological approach to investigate how Generation Z constructs and manages impressions through text-based communication. Data were collected from 15–20 participants via in-depth interviews, digital conversation analysis, and online observations. The findings reveal that Typing Ganteng serves as a strategic tool for impression management, helping users convey a friendly and trustworthy persona. This style also reflects broader digital cultural norms, including gender-neutral politeness and communication consistency across platforms. The study contributes to communication scholarship by positioning text as a performative medium for identity expression. Ultimately, Typing Ganteng is not merely a stylistic trend but a deliberate interpersonal strategy shaped by the expectations of digital culture.